Nurses’ attitudes towards alcoholism: factor analysis of three commonly used scales - Pillon, Sandra; Laranjeira, Ronaldo; Dunn, John (São Paulo Medical Journal, 1998)
OBJECTIVE: To investigate the psychometric properties of three scales commonly used to measure attitudes and beliefs about alcoholism. DESIGN: Cross-sectional study using a systematic sample. SETTING: Hospital São Paulo (a public general tertiary hospital) and the adjoining Federal University of São Paulo, Brazil. PARTICIPANTS: 310 nurses and nursing teachers. INSTRUMENTS: The Marcus Alcoholism Questionnaire, The Seaman Mannello Nurses’ Attitudes Towards Alcohol and Alcoholism Scale and The Tolor-Tamarin Attitudes Towards Alcoholism Scale, which were combined into one self-administered questionnaire. ANALYSIS: The scales were re-grouped into their original formats and each underwent a principal components analysis with orthogonal rotation of factors. RESULTS: Each scale was found to consist of three main factors. There was some degree of overlap in the nature of the factors that the scales measured but each scale also measured something unique. COCLUSION: The results of this comparative analysis could be used as a basis for developing a new scale covering all the important attitudinal groups identified by this study.